The The Effect of The Use of The Who Contraception KB Application on Women of Fertile Age (WUS) in The Knowledge of Choosing Contraception Devices - Nurul Fitria Nopianti; Sofa Fatonah; Resi Alpia Julianti (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Family planning is an action that helps husband and wife avoid unwanted pregnancies, regulate the interval between pregnancies, control the time of birth in relation to the age of the husband and wife, and determine the number of children in the family, according to the WHO (World Health Organization).Statistical data from the BKKBN shows that the achievement of new KB participants has decreased significantly from 422,315 in March 2024 to 371,292 and 388,390 in April-May 2024. The decrease in contraceptive use also includes implants which fell from 81,062 to 51,536, injections to 341,109. The purpose of the study To determine the effect of the use of Android Applications on Women of Childbearing Age (WUS) in choosing contraceptives. The research design was pre-experiment with type one group pretest-postest., sample 40 respondents, this study used Paired sample t-Test. The population in this study was 138 people, the sample in this study was 40 people by purposive sampling. The results of the study had good knowledge of 37 people (92.5%), there was an effect of the use of the WHO Contraception application on knowledge. Respondents' knowledge was good 37 people (92.5%) after being given the WHO contraception application, there was an effect on the knowledge of women of childbearing age after being given the WHO contraception application, so this shows that the use of the WHO Contraception application in choosing contraceptives can increase the knowledge of women of childbearing age.